Legal Effects Of Making A Testament On The Inheritance Rights Of Members Of The Society Of Jesus (Pastors) Who Resign According To The Civil Code (Study In The Provincial State Of The Society Of Jesus Semarang) - Alma Aditya Permana, Benedikta; Taruno Muryanto, Yudho; Budi Kharisma, Dona (International Journal of Educational Research & Social Sciences, 2025)
This thesis examines and analyzes the legal consequences of making a testament and the mechanisms for resolving inheritance rights of members of the Society of Jesus (priests) who have made a testament and later resigned, according to the Indonesian Civil Code ( KUHPerdata ). The study was conducted at the Provincial House of the Society of Jesus in Semarang. The research method used is empirical legal research, employing interviews and literature review approaches. The results of the research show that, according to the Indonesian Civil Code, the legal consequence for a former priest who has made a testament and then resigned is that he remains bound by the testament he previously made. The Society of Jesus community or the Aloysius Association retains its position as the testamentary heir of the former priest, based on the legal grounds of Article 954 of the Civil Code. According to Articles 913–914 of the Civil Code, a testament that has not been revoked can affect the portion of inheritance and determine the subject entitled to the inheritance of the former priest. As a result, it may reduce the legitimate share (legitime share ) of the former priest's family members, including biological children (if married) or biological parents as legataris (recipients of the legitimate portion). For former priests who were leaders of a foundation or institution managed by the Society of Jesus, whose names were used for purposes such as purchasing land under ownership rights, opening bank accounts, or receiving donations, a process of name transfer (re-registration) can be carried out.